MELODI DAN LIRIK LAGU CAMPURSARI CIPTAAN MANTHOUS - -, Kusnadi (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
Campursari songs are specific phenomena in music development and Javanese traditional music. Based on forms, campursari songs composed by Manthous still refer to traditional music and songs, especially the conventional ones, lelagon dolanan, or mixture between them. The most dominant literary decoration applied in his song lyrics are purwakanthi guru swara, parikan, wangsalan, wancahan, the change of vowels at the end of stanzas, traditional expressions, senggakan and bebasan paribasan. The most dominant themes are love, marriage life, beauty of nature and social life. All are in accordance with the target of audience, namely youths and adults. Keywords: melody, lyrics, campursari songs